Intensity and directionality of emotion in sport competition: Why does it matter? - Nicolas, M.; Levillain, G.; Saby, Y.; Vacher, P.; Cece, V.; Martinent, G. (Proceedings of AC 2019, Prague 8.-10. August 2019, 2019)
Objectives: The aims of this research were: (a) to provide the best way to represent the factor structure of sport emotion questionnaire - direction (SEQ-D) scores using advanced techniques recently introduced in the literature, and (b) to examine differential item functioning (DIF) as a function of sex on the SEQ-D responses. Method: A total of 363 athletes (M = 18.69, SD = 1.11) completed the SEQ-D. Data were analysed with a series of: (1) confirmatory factorial analysis (CFA), bi-factor and exploratory structural equation modeling (ESEM) for the factorial structure; and (2) multiple indicators multiple causes (MIMIC) for testing associations between SEQ-D scores and sex. Design: Cross-sectional with self-reported questionnaires. Results: Based on the indices of fit and standardised factor loadings, results suggested that the ESEM model could be considered as the best model to describe the factorial structure of SEQ-D scores. Moreover, the results from the MIMIC models did not reveal DIF for sex highlighting no bias in relation to that demographic variable. Conclusion: The findings indicate that sport psychologists should consider both intensity and direction of emotion in their counter-measures in order to maximize both the performance and psychological adjustment of athletes.